Iranian Risk-Oriented Service Contracts as a Mechanism for Attracting Investments in the Oil and Gas Sector - A. S. Mal’tsev (Учёт. Анализ. Аудит)
The article contains an overview of the mechanisms for attracting production and technological investments of transnational companies in the development of hydrocarbon deposits and a detailed analysis of the national experience of the Islamic Republic of Iran in this area. The results of the analysis of the evolutionary development of four generations of Iranian service contracts showed that the mechanism developed by the Iranian government made it possible to restore oil production in the country to the peak levels of the 70s of the last century and at the same time to ensure the protection of national interests from the withdrawal of excess income by investors. It is argued that in the near future, the Russian hydrocarbon industry will continue to develop new projects together with foreign oil and gas companies. During the research, analytical and graphical methods of comparison and generalization were used. The need for further in-depth study of the Iranian experience in the development of the hydrocarbon sector and its application in the oil and gas sector of the Russian Federation, taking into account the structural features, has been proved. The study may be of interest to specialists from federal authorities with the aim of developing the Russian energy sector and ensuring the protection of national interests.